The Impact of Social Networks on Changing Values - Jwan Ismail Bakir; Trifa Sabir Aziz (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Social networks are one of the most significant influences of communication in the world, it has lots of users that are considered at the service of individuals and society in many areas of life. This great progress has had many effects on changing the individual system. It causes a huge reflection on the rules of freedom of publication, and appearance, creates channels for communication and information sharing both within and between segments of society. Technology has entered their lives and significantly influenced their way of life. New technology and social networks had also expanded and unlimited individuals' desires, hobbies, and aspirations, resulting in greater use as well as societal values and criteria becoming impactful, Values are a set of criteria and rules that guide individuals to organize their behavior in society, so from this perspective, the study aims to explain how social networks influence the change of university students' values. In this study, the descriptive method of social survey is used. The research used Quantitative method and descriptive approach and the scale was used as the main tool of data collection, Then the analysis and presentation of the data in which the results of the study are presented and based on the results of the study, some recommendations and suggestions are discussed.